Electrical and thermal properties of insulating oil-based nanofluids: a comprehensive overview. Issue 1 (11th February 2019) - Huang, Zhengyong; ,; , Jian Li; Yao, Wei; Wang, Feipeng; Wan, Fu; Tan, Yaxiong; Mehmood, Muhammad Ali
No abstract available